Laboratory friction measurements of high-grade minerals - Ikari, Matt J; Fagereng, Åke (PANGAEA, 2020)
Here, we present the results of laboratory shearing experiments on chlorite schist, epidotite, and a hornblende-dominated amphibolite, and mixtures of these rocks, and evaluate their frictional properties and microstructures.
Keywords: chlorite; epidote; fault; friction; hornblende; retrograde